Functional characterization of the first filamentous fungal tRNA-isopentenyltransferase and its role in the virulence of Claviceps purpurea - Hinsch, Janine; Galuszka, Petr; Tudzynski, Paul (The New phytologist, 2016)
In plants, cytokinins (CKs) are synthesized de novo or by the degradation of modified tRNAs. Recently, the first fungal de novo pathway was identified within the plant pathogen Claviceps purpurea. As the deletion of the de novo pathway did not lead to a complete loss of CKs, this work focuses on the tRNA-modifying protein tRNA-isopentenyltransferase (CptRNA-IPT). The contribution of this enzyme to the CK pool of Claviceps and the role of CKs in the host-pathogen interaction are emphasized. The effects of the deletion of cptRNA-ipt and the double deletion of cptRNA-ipt and the key gene of de novo biosynthesis cpipt-log on growth, CK biosynthesis and virulence were analyzed. In addition, the sites of action of CptRNA-IPT were visualized using reporter gene fusions. In addition to CK-independent functions, CptRNA-IPT was essential for the biosynthesis of cis-zeatin (cZ) and contributed to the formation of isopentenyladenine (iP) and trans-zeatin (tZ). Although ΔcptRNA-ipt was reduced in virulence, the 'CK-free' double deletion mutant was nearly apathogenic. The results prove a redundancy of the CK biosynthesis pathway in C. purpurea for iP and tZ formation. Moreover, we show, for the first time, that CKs are required for the successful establishment of a host-fungus interaction.
Keywords: biotest; Virulence; tRNA degradation pathway; Substrate Specificity; delece genu; RNA, Transfer; fungální léková rezistence; host-pathogen interaction; Drug Resistance, Fungal; alkyltransferasy a aryltransferasy; cytokininy; Cytokinins; Claviceps; virulence; Alkyl and Aryl Transferases; Mycelium; Gene Deletion; tRNA-isopentenyltransferase (tRNA-IPT); mycelium; Claviceps purpurea; cytokinin (CK) biosynthesis; Biological Assay; RNA transferová; Fungicides, Industrial; Isoenzymes; průmyslové fungicidy; substrátová specifita; izoenzymy